Mark of evil ebook - LaHaye, Tim (The End Series, 2023)
In the final installment of The End series, economies have collapsed, freedom has been suppressed, and peace is a distant memory. The world is falling apart. Joshua Jordan’s protégé Ethan March, along with Jimmy Louder and Rivka Reuban, have been left behind in a world that is rapidly coming under the complete influence of the Antichrist. Technology is growing by leaps and bounds with BID-Tag implants, robotic police units, and drone-bots flying overhead . . . all designed to control and dominate those who resist the Antichrist’s reign of evil. As Biblical prophecy is fulfilled each new day, Ethan and the others in the Remnant struggle to eat, to procure necessary goods, and to avoid the Global Alliance—in short, to survive. But when the forces of evil attempt to pervert the world’s most powerful information system to their own sinister ends, eliminating everyone who gets in their way, it’s up to Ethan and the Remnant to subvert their dark ambitions. From New York Times bestselling author Tim LaHaye, creator and co-author of the world-renowned Left Behind books, Mark of Evil is the final thrilling chapter to The End series. Futuristic Christian political thriller The final installment of The End series Book 1: Edge of Apocalypse Book 2: Thunder of Heaven Book 3: Brink of Chaos Book 4 : Mark of Evil Includes discussion questions for book clubs